Disruptive Mood Dysregulation Disorder Symptoms by Age in Autism, ADHD, and General Population Samples. Issue 4 (2nd October 2017) - Mayes, Susan Dickerson; Kokotovich, Cari; Mathiowetz, Christine; Baweja, Raman; Calhoun, Susan L.; Waxmonsky, James
ABSTRACT: Disruptive mood dysregulation disorder (DMDD) is a controversial DSM-5 diagnosis. It is not known how DMDD symptoms vary by age and if differences are similar for autism, ADHD, and general population samples. Our study analyzed the two DMDD symptoms (irritable-angry mood and temper outbursts) in 1, 827 children with autism or ADHD (with or without oppositional defiant disorder/ODD) and 657 general-population children 2–16 years of age. DMDD symptoms were rated by mothers on the Pediatric Behavior Scale. For all age groups, mean DMDD scores were less than sometimes a problem in the general population and ADHD-Inattentive (ADHD-I) samples, greater than sometimes but less than often a problem in autism and ADHD-Combined (ADHD-C), and greater than often a problem in children with autism or ADHD who also had ODD. DMDD symptoms were unrelated to age in children six and older. Preschool children with ADHD-C, ADHD-I, and ODD had more DMDD symptoms than school-age children, but DMDD symptoms did not differ by age in autism. DMDD symptoms were found in 45% of children with autism and were common at all ages. Evidence-based interventions are discussed.